Pelatihan Pengendalian Internal pada Siklus Penjualan dan Dasar Pencatatan Akuntansi pada BUMDes Mitra Mandiri - Fitriyeni Oktavia; Sanda Patrisia Komala Sari; Berri Briliant Albar; Ares Albirru Amsal (Warta Pengabdian Andalas, 2023)
BUMDes is a village-owned enterprise that aims to strengthen the village economy. In order to realize the goals, a system is needed to prevent, reduce and correct errors and fraud that can hinder the goals and sustainability of BUMDes. According to COSO (Committee of Sponsoring Organization of Treadway), internal control is a method or system used to achieve company goals effectively and efficiently. The Community service team from Universitas Andalas conducted training on internal control to increase BUMDes teams' understanding of the importance of internal control in business operations. BUMDes Mitra Mandiri owns business units engaged in buying and selling fuel and building materials, so the training focuses on the scope of the sales cycle. This activity aims to provide BUMDes managers with an understanding of the importance of internal control in operations and to assist and guide managers in implementing reasonable internal control in the sales cycle and keeping correct accounting records. This activity was carried out through practical training and coaching. The benefit of this activity was that BUMDes teams understand the importance of internal control in the sales cycle to increase operational effectiveness and efficiency, maintain assets and prevent and repair errors and damage that can collapse the BUMDes businesses.